Advances in mass spectrometry‐based glycomics. Issue 24 (9th October 2018) - Dong, Xue; Huang, Yifan; Cho, Byeong Gwan; Zhong, Jieqiang; Gautam, Sakshi; Peng, Wenjing; Williamson, Seth D.; Banazadeh, Alireza; Torres‐Ulloa, Katya Y.; Mechref, Yehia
Abstract: The diversification of the chemical properties and biological functions of proteins is attained through posttranslational modifications, such as glycosylation. Glycans, which are covalently attached to proteins, play a vital role in cell activities. The microheterogeneity and complexity of glycan structures associated with proteins make comprehensive glycomic analysis challenging. However, recent advancements in mass spectrometry (MS), separation techniques, and sample preparation methods have primarily facilitated structural elucidation and quantitation of glycans. This review focuses on describing recent advances in MS‐based techniques used for glycomic analysis (2012–2018), including ionization, tandem MS, and separation techniques coupled with MS. Progress in glycomics workflow involving glycan release, purification, derivatization, and separation will also be highlighted here. Additionally, the recent development of quantitative glycomics through comparative and multiplex approaches will also be described.